Finance Shared Service Delivering Value : A GE Global Business Services (Asia) - Ching Sim, Tan (2008)
The role of Finance and Accounting function has been evolving. It was found that the role of finance has expansively been broadened from the conventional times of back-office responsibilities in book keeping as score keeper and been elevated to become a fully-involved and engaged business partner working with cross-functional team to deliver and increase value to the overall organization in the capacity as a score maker. This requires the Finance organization to be transformed and one of the commonly deployed approach is the set-up of a Shared Service Centre. The era of Shared Service began sometime in the 1990s. In the beginning, only simple transactional type of work such as Accounts Payable and Payroll would be moved to the Shared Service Centre. Over time, with the Shared Service Centre becoming more matured, the Centre has gained the scale and capability to undertake higher value work that could include Financial Analysis, Treasury or Tax related work. Finance Shared Service Centre are now able to deliver more value to the business. These values include improving efficiency, strengthening controls and compliance, driving internal customer satisfaction, enabling focus on business growth, developing talent pipeline and cost savings. For the purpose of this research, the case study of General Electric’s (GE) shared service arm named Global Business Services (GBS) Asia)is being examined. Using an interview-based approach with key personnel in leadership roles from GBS Asia and the Business, it was found that the shared service strategy for General Electric is working well and delivering the values mentioned earlier to the company. Nevertheless, there is a major concern. Full execution is very challenging for a huge company like General Electric as the business portfolio is very diversified and further complicated by different systems platforms.